Biofuels, international food prices, and the poor - von Braun, Joachim (International Food Policy Research Institute, 2008)
World agriculture is at a turning point: economic growth, energy needs, and climate change redefine the equations of agricultural supply and demand and contribute to accelerate food prices. Biofuels have been particularly high on the global agenda largely due to rising concerns about national energy security, high energy prices, and global climate change, as well as the income expectations of farmers and other investors (von Braun and Pachauri 2006). The International Grain Council reports an overall growth in the use of cereals by 32% in 2007/8 and an estimated 31% in the coming year, and by 41% and 32% in the USA respectively (see table 1). The USA has a share of about 80% in the total quantity. The total quantity used globally this year (95 Mill. Tons) is large, relative to total world trade of corn (100 Mill. Tons) and relative to total world corn production (777 Mill. Tons). The rapid expansion of ethanol and biodiesel has increased dependency on natural vegetation and crops grown specifically for energy. Biofuel production has also introduced new food-security risks and new challenges for the poor, particularly when resource constraints have lead to trade-offs between food and biofuel production and rising food prices. For the further development and use of biofuels, it is necessary to carefully assess the impact of different technologies, products (ethanol, bio-diesel, bio-gas), and feed stocks (e.g. sugar cane, corn, oilseeds, palm oil, agricultural waste and biomass).